PENERAPAN MODEL PEMBELAJARAN TGT (TEAMS GAMES TOURNAMENT) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI TELADAN MULIA ASMAUL HUSNA KELAS IV SD NEGERI 1 PAGAK KECAMATAN PAGAK - Hidayati, Trifika; Sholeh, Ahmad; Hambali, Muh (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
This research is based on the problem (1) How does the TGT (Teams Games Tournament) learning model apply in improving the learning outcomes of Class IV students for the 2022/2023 academic year on the Asmaul Husna Noble Example material? (2) How can the learning outcomes of noble Asmaul Husna's exemplary material be improved through the application of the TGT (Teams Games Tournament) learning model for Class IV students at SD Negeri 1 Pagak for the 2022/2023 academic year? Meanwhile, the objectives of this research are (1) To describe the application of the TGT (Teams Games Tournament) learning model in improving the learning outcomes of Class 4 students for the 2022/2023 academic year on the material of Asmaul Husna's Noble Example. (2) Describe the improvement in learning outcomes of Class 4 students for the 2022/2023 academic year on the Noble Asmaul Husna Example material through the application of the TGT (Teams Games Tournament) learning model. This research uses three rounds of action research. Each round consists of four stages, namely: Action Planning, Action, observation and reflection. The target of this research is class IV students for the 2022-2023 academic year. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the analysis results, it was found that student learning achievement increased from cycle I to cycle II, namely, cycle I (67%), cycle II (93%). Conclusions from this research 2. Learning PAI material from Mulia Asmaul Husna's Example in class IV of SD Negeri 1 Pagak through the TGT Learning Model for class IV students of SD Negeri 1 Pagak has encouraged an increase in student learning outcomes. This can be proven by the increase in the value of the percentage of completeness of students, where in the pre-cycle the percentage of completeness of students' learning outcomes only reached 33%, while in cycle I it increased to 67%, and in cycle II it increased again to 93%. This shows that the Class Action Assessment research was declared successful, because the target for achieving PTK completeness was 90% while the results exceeded the planned target, namely reaching 93%. Abstrak Penelitian ini berdasarkan permasalahan (1) Bagaimana penerapan model pembelajaran TGT ( Teams Games Tournament) dalam meningkatkan hasil belajar peserta didik Kelas IV tahun pelajaran 2022/2023 pada materi Teladan Mulia Asmaul Husna? (2) Bagaimana peningkatan hasil belajar materi teladan mulia asmaul husna melalui penerapan model pembelajaran TGT (Teams Games Tournament) peserta didik Kelas IV SD Negeri 1 Pagak Tahun Pelajaran 2022/2023 ? Sedangkan tujuan dari penelitian ini adalah (1) Mendeskripsikan penerapan model pembelajaran TGT ( Teams Games Tournament) dalam meningkatkan hasil belajar pesertadidik Kelas 4 tahun pelajaran 2022/2023 pada materi Teladan Mulia Asmaul Husna. (2) Mendeskripsikan peningkatan hasil belajar pesertadidik Kelas 4 tahun pelajaran 2022/2023 pada materi Teladan Mulia Asmaul Husna melalui penerapan model pembelajaran TGT ( Teams Games Tournament). Penelitian ini menggunakan penelitian tindakan (action research) sebanyak tiga putaran. Setiap putaran terdiri dari empat tahap yaitu : Perencanaan Tindakan, Tindakan, observasi dan refleksi. Sasaran penelitian ini adalah siswa kelas IV Tahun pelajaran 2022-2023. Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar. Dari hasil analis didapatkan bahwa prestasi belajar siswa mengalami peningkatan dari siklus I sampai siklus II yaitu, siklus I (67%), siklus II (93%). Simpulan dari penelitian ini 2. Pembelajaran PAI materi Teladan Mulia Asmaul Husna di kelas IV SD Negeri 1 Pagak melalui Model Pembelajaran TGT pada peserta didik kelas IV SD Negeri 1 Pagak telah mendorong peningkatan hasil belajar peserta didik. Hal ini dapat dibuktikan dengan meningkatnya nilai prosentase ketuntasan peserta didik yang pada pra-siklus prosentase ketuntasan hasil belajar peserta didik hanya mencapai 33%, sementara pada siklus I meningkat menjadi 67%, dan pada siklus II meningkat kembali menjadi 93 %. Hal ini menunjukkan bahwa penelitian Penilaian Tindakan Kelas dinyatakan berhasil, karena target pencapaian ketuntasan PTK adalah 90% sedangkan hasilnya melebih dari target yang direncanakan yaitu mencapai 93%.